(untitled) - Võ, Thị Diễm My (Cần Thơ, 2020)
The present study investigated the effect of idiom instruction, specifically the use of 3 techniques-using contextual clues, L1 L2 idiom comparison and using pictures, on EFL teenage learners’ retention of idiomatic knowledge at a private language center in the Mekong delta. To achieve the aim of the study, the researcher employed the quasi experimental research approach (one group design with pre and posttest). The sample of the consisted of 37 teenage participants study, purposely selected at pre-intermediate level of proficiency. The focus was on idiom knowledge: both form, meaning as well as the use of the frequently used idioms. A pre-study was conducted to gauge 76 teenage learners’ knowledge by a piloting test of 50 common idioms which resultedin these learners’ limited idiomatic knowledge. This shed the light to the significance of this study. Taking advantages of the piloting test, 35 idioms most un-known were given by a redesigned test (IKT) in the experiment to ensure the participants’ unfamiliarity of the idioms. The idioms that were known even by one student were crossed out and at the end 30 idioms were screened, selected for the treatment with IKT pretest result as 0. Accompanying with the intervention-3 techniques above respectively applied for 2 weeks each, the VKSIT subtests were utilized to test effect of each technique before and after being exploited. The researcher designed 6 lesson plans followed PPP model, integrated with explicit instruction and meaningful learning principles, as well as interactions. The treatment was completed in 7 weeks and then 18 individuals randomly invited to take part in interviews to gain insights about learners’ attitudes towardstheir idiom learning. At week 11, an IKT posttest was delivered to achieve the answers regarding effect of idiom instruction. The findings showed that all of the participants’ posttest results in both IKT and VKSIT were much higher than their pretest results.
Keywords: English language,Anh ngữ; Idiom,Thành ngữ